2020
DOI: 10.1016/j.heliyon.2020.e04337
|View full text |Cite
|
Sign up to set email alerts
|

Catechin profile and hypolipidemic activity of Morinda citrifolia leaf water extract

Abstract: Cardiovascular diseases (CVDs) are silent killers and hyperlipidemia is a high-risk factor. Morinda citrolia leaf (MCL), which is commonly consumed by many cultural groups and has high level of catechins, might exert antihyperlipidemic properties. In this study, the catechins profile of MCL water extract was determined via HPLC and ultraperformance liquid chromatography-traveling wave ion mobility-quadrupole time of flight mass spectrometry (UPLC-TWIMS-QTOF). The major catechin in MCL and the most widely studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This plant possessed anti-inflammatory, antidyslipidemic, and antioxidant properties from the isolation of β-carotene, kaempferol, quercetin, rutin, and ursolic acid. An experiment on the antiatherosclerotic properties of M. citrifolia leaf extract revealed lipid elimination and antiinflammatory activity (Kah Hui et al, 2020). The antioxidant test was evaluated using the DPPH radical method, resulting in a dose-dependent response higher than that of ascorbic acid.…”
Section: Genus Morindamentioning
confidence: 99%
“…This plant possessed anti-inflammatory, antidyslipidemic, and antioxidant properties from the isolation of β-carotene, kaempferol, quercetin, rutin, and ursolic acid. An experiment on the antiatherosclerotic properties of M. citrifolia leaf extract revealed lipid elimination and antiinflammatory activity (Kah Hui et al, 2020). The antioxidant test was evaluated using the DPPH radical method, resulting in a dose-dependent response higher than that of ascorbic acid.…”
Section: Genus Morindamentioning
confidence: 99%
“…Their results showed that A. niger and A. tubingensis produced eriodictyol, while A. japonicus and A. aculeatus produced taxifolin and catechin. These phenolic compounds have several health benefits: eriodictyol is a flavonoid with broad biological and pharmacological effects [231], including anti-inflammatory effect in osteoarthritis [232], cardioprotective effect [233], control of blood vessels permeability [234] and anti-allergic effect [235]; taxifolin is also a flavonoid with biological activities at different levels, showing antioxidant [236], antibacterial, anti-inflammatory [237] and antiviral [238] activities, improving microcirculation and regulating immunity, being used for treatment of atherosclerosis, dyslipidemia, cardiovascular diseases and other chronic diseases [239,240]; catechin, again in the class of flavonoids, has proven beneficial in cardiovascular health and showing several effects on the human body [241], like antioxidant [242], antihypertensive [243], anti-inflammatory [244], antiproliferative [245] and anti-hyperlipidemic [246].…”
Section: Health Effects Of Fermented Apple Productsmentioning
confidence: 99%
“…and antioxidant [10], anti-obesity metabolomics [11], and antidiabetic properties [12], and research [13] on the bioactive components of butterfly pea flower which showed antioxidant, antihemolytic and antihypertensive effects, inhibiting the activity of α-amylase and αglucosidase and reducing LDL cholesterol and DNA induced oxidation. Research on noni leaves has also been carried out in parallel with research on noni fruit, including testing the anti-oxidative properties of noni leaves, roots and fruit [14], antioxidant, antiinflammatory, stress response properties [15], catechins and hypolipidemic activity [16], chemical composition, biological activity and toxicity of noni leaves and fruit [17], and profiling of noni leaf polyphenols and antioxidants [18].…”
Section: Introductionmentioning
confidence: 99%